Hypermedia systems modelling framework - Dolog, Peter; Bieliková, Mária (Computing and Informatics, 2012)
Modelling is an important activity in the development of complex systems. Hypermedia modelling is a relatively new direction of research. Based on achieved results in software systems development, the recognition of importance of hypermedia modelling took relatively short time from the time of widespread adoption of hypermedia systems. However, the hypermedia modelling is not that mature as its software counterpart. The aim of this paper is to present a survey of hypermedia systems modelling along proposed five perspectives: hypermedia application perspective, development process perspective, aspect (static or dynamic) perspective, degree of formality, and notation perspective. First, a categorisation of hypermedia related models is proposed. According to this categorisation, the multidimensional modelling space is established. The space leads to a schema that is capable to support decisions about the reuse of methods and techniques for hypermedia systems modelling. Additionally, selected hypermedia modelling methods and techniques with their mutual dependencies are studied according to the proposed categorisation.